Alpha glucosidase inhibition activity of phenolic fraction from Simarouba glauca: An in-vitro, in-silico and kinetic study - Kirana P. Mugaranja; Ananda Kulal (Heliyon, 2020)
A phenolic rich fraction purified from Simarouba glauca leaves was effective in alpha glucosidase inhibition. The purified fraction named ‘fraction-14’ had shown significant inhibition of yeast alpha glucosidase enzyme activity (IC50 = 2.4 ± 0.4 μg/mL) when compared to anti-diabetic drug acarbose (IC50 = 2450 ± 24 μg/mL). The purified fraction also had reasonable DPPH (IC50 = 14.4 ± 0.1 μg/mL) and ABTS (IC50 = 7.6 ± 0.5 μg/mL) free radical scavenging activity when compared to the standard ascorbic acid. The LC-MS analysis of bioactive ‘fraction-14’ revealed four compounds, eclalbasaponin-v (1), cyanidin-3-O-(2′galloyl)-galactoside (2), kaempferol-3-O-glucoside (3) and kaempferol-3-O-pentoside (4) for the first time in S. glauca in this study. The kinetic study of the ‘fraction-14’ indicates a mixed type of inhibition on the alpha glucosidase enzyme with Ki, 6.2 μg/mL. Docking studies showed promising binding energy for the compounds 2 (-7.769 kJ/mol), 3 (-7.04 kJ/mol) and 4 (-7.127 kJ/mol) against yeast alpha glucosidase which was better than acarbose (-6.867 kJ/mol). In conclusion, the phenolic rich fraction from S. glauca possessing good in-vitro antioxidant property and alpha glucosidase enzyme inhibition potential along with mixed inhibition kinetics. Also, better binding energy of compounds (1, 2 & 3) appears to contain potential lead-molecule for antidiabetic therapy.